Teaching Listening Through Real-World English: VOA Videos at SMP Negeri 13 Makassar - Nirwana; Ampa, Andi Tenri; AS, ST. Asmayanti (FKIP Unismuh Makassar, 2025)
This study investigates the effectiveness of Voice of America (VOA) videos as a medium for improving students’ English listening skills and examines student responses to this media. Using a pre-experimental design, data were collected through pre-tests, post-tests, and a questionnaire involving 30 eighth-grade students at SMP Negeri 13 Makassar. The results revealed a significant improvement in students’ listening performance, with mean scores increasing from 70.43 (pre-test) to 86.00 (post-test), reflecting a 22.10% gain. Statistical analysis showed a t-test value of 130.6, exceeding the t-table value of 2.045 (p < 0.05), confirming the significance of the improvement. Student responses to the use of VOA videos were mixed, with a tendency toward neutrality and disagreement. These findings suggest that while VOA videos can effectively enhance listening skills, student engagement and perception may vary. This study contributes to the existing literature on the integration of authentic multimedia in language instruction, particularly in listening comprehension.